Diffusion tensor imaging findings of the median nerve before and after carpal tunnel corticosteroid injection in patients with carpal tunnel syndrome: a preliminary study. (March 2019) - Hsu, Yi-Chih; Yang, Fu-Chi; Hsu, Hsian-He; Huang, Guo-Shu
Background: Corticosteroid injections are a popular technique for carpal tunnel syndrome (CTS) treatment and are believed to provide rapid symptom relief. Purpose: To use magnetic resonance diffusion tensor imaging (MR-DTI) to determine the association between diffusion values of the median nerve (MN) at several anatomic locations and symptom relief in patients with CTS following corticosteroid injection. Material and Methods: MR-DTI was performed on 15 wrists of 12 patients with CTS before and two weeks after ultrasound-guided corticosteroid injections. We recorded the patients' clinical data including sex, age, side of injection, satisfaction, and symptom relief. Satisfaction and symptom relief were rated using a Likert scale and the Boston Carpal Tunnel Syndrome Questionnaire (BCTQ) scale. Fractional anisotropy (FA) and apparent diffusion coefficient (ADC) of the MN at the levels of the distal radioulnar joint (DRUJ), pisiform bone, and hamate bone were determined. Results: All patients had ≥50% satisfaction on the injection side. In comparison with baseline values, post-injection ADC was significantly lower ( P  = 0.001) but FA was not significantly higher ( P  = 0.11) at the pisiform bone level on the injected wrists. At the DRUJ and hamate bone levels, no obvious inter-scan change in FA and ADC ( P  > 0.05) was observed. The decrease in ADC at the pisiform bone level strongly correlated with the decrease in BCTQ scores (r = 0.628; P  = 0.012). Conclusion: Symptom relief in patients with CTS receiving corticosteroid injection is related to the change in ADC of the median nerve at the level of the pisiform bone, as determined using MR-DTI.